Facilitating Novice Writers with Creative Writing Workshop in Poetry Writing Classroom (Indonesian EFL Context) - Winda Setia Sari; Juli Rachmadani Hasibuan; Citra Anggia Putri (Budapest International Research and Critics in Linguistics and Education (BirLE) Journal, 2020)
The increasing usage of creative writing strategy in a poetry writing classroom can nevertheless answer the question which has been empirically explored throughout the decade; Can second language learner write a poem in their non-native tongue? This study aimed to answer whether the creative writing strategy can facilitate novice writers who are the third year of English Department undergraduate students to be able to write an English poem. The strategies cover written prompts dealing with their personal experience and memory. After conducting two series of creative writing workshop, the result conveys that second language novice writers demonstrate the ability to communicate their personal experience dealing with their significant others. Repetition of words and grammatical error exist, yet most writers can produce longer poems with complexities. Also by providing the novice writers with written prompts, students find themselves more enthusiastic and eager to write.